The Effect of Critical Thinking Strategy on Students' Motivation in EFL Speaking Class - Muhammad Wiranto; Syarifuddin Dollah; Maemuna Muhayyang (ARRUS Journal of Social Sciences and Humanities, 2024)
This research was to analyze the effect of critical thinking strategy on students’ motivation in speaking class in the first year of the English Education Department, UIN Alauddin Makassar. It employed a quantitative approach with a true experimental design. Its population was the first-year students of the English Education Department consisting of 20 students as the experimental group and 20 students as the control group. A questionnaire was used to find out the students’ motivation to see the effect of critical thinking strategy in speaking class. This research results show that the mean score of students’ motivations in the experimental class was categorized into a positive level (80.75) in the pre-questionnaire and a very positive level in post- questionnaire (97) meaning that there was a significant increase in students’ motivation in speaking class. Conversely, the student's motivation in the control group was categorized into a very positive level (83.45) in the pre-test and a very positive level (88.6) in the post-questionnaire meaning that the student’s motivation was stable. Moreover, the calculation statistics of the Mann-Whitney U test of students’ motivation are valued at sig. 0.020 < 0.050 figuring out that critical thinking strategy affected the students’ speaking motivation in the control group. These findings take into account that the students were to speak comprehensively as a discipline, to maintain speaking achievement as a satisfaction, and to create a feeling of safety in the speaking process as a security.